Efektivitas Layanan Bimbingan Konseling Kelompok Terhadap Konsep Diri Remaja Korban Bully di SMK Negeri 1 Lotu - Dirga Krisna Zega; Hosiana R. Damanik; Famahato Lase; Mondang Munthe (Departement of Mathematics Education, 2024)
Based on the results of interviews with several teachers, it was found that grade X students of SMK Negeri 1 Lotu still have many teenage students who have poor self-concept due to the bullying actions they receive. As for several factors that cause poor self-concept of adolescent students From these findings, researchers made a study with the aim of knowing the picture of changes in the self-concept of bully victim students in class X of SMK Negeri 1 Lotu through group counseling guidance services.This study uses quantitative methods with a descriptive approach, with the formulation of the research problem describing the results of group counseling guidance to students who are victims of bullying seen from the level of student self-concept. In this case, researchers distributed questionnaires to find out the level of students' self-concept and then counseling guidance was carried out on students who had a high level of bullying. The results of this counseling guidance will be described using percentages. The number of samples distributed by the self-concept questionnaire was 100 people. The results stated that the self-concept of bully victims at SMK Negeri 1 Lotu was classified as